2020
DOI: 10.1097/md.0000000000021578
|View full text |Cite
|
Sign up to set email alerts
|

The effect on deep brain stimulation of subthalamic nucleus and dopaminergic treatment in Parkinson disease

Abstract: Impulsivity is a frequent non-motor symptom in Parkinson disease (PD). It comprises psycho-behavioral alterations that negatively impact quality of life. Dopaminergic treatments underpin many impulsive controls disorders however, side effects, such as increased impulsivity, are described also after neurosurgical procedure of deep brain stimulation (DBS). We investigated the effect of deep brain stimulation on psycho-behavioral alterations and quality of life (QoL) in PD patients, analyzing, also, the role of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Whether non-pharmacological interventions such as deep brain stimulation (DBS) ameliorates or worsens ICRBs in PD patients is still debated. While most human studies indicated that DBS improves PD + ICD, some have reported the development of short-term de novo ICDs following DBS ( Amami et al, 2015 ; Rossi et al, 2017 ; Kim et al, 2018 ; Lo Buono et al, 2020 ; Santin et al, 2020 ). In rodents, decreased risk-taking and loss-chasing was reported following lesioning to the subthalamic nucleus (STN), possibly pinpointing this region as a target for DBS and other treatments for PD + ICD ( Breysse et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether non-pharmacological interventions such as deep brain stimulation (DBS) ameliorates or worsens ICRBs in PD patients is still debated. While most human studies indicated that DBS improves PD + ICD, some have reported the development of short-term de novo ICDs following DBS ( Amami et al, 2015 ; Rossi et al, 2017 ; Kim et al, 2018 ; Lo Buono et al, 2020 ; Santin et al, 2020 ). In rodents, decreased risk-taking and loss-chasing was reported following lesioning to the subthalamic nucleus (STN), possibly pinpointing this region as a target for DBS and other treatments for PD + ICD ( Breysse et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive motor impulsivity may lead to difficulty with response inhibition. Hence, failing to resist temptations may result in relapse and acting impulsively may contribute to conflicts with others ( 24 , 105 , 106 ). Another important edge identified in this study was the positive connection between BASR “BAS-reward responsiveness” and PSU5 “withdrawal,” which is similar to the finding that BASR is a predictor of PSU ( 25 ).…”
Section: Discussionmentioning
confidence: 99%